2018
DOI: 10.1038/s41598-018-31550-y
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular dysfunction in ankylosing spondylitis is associated with disease activity and is improved by anti-TNF treatment

Abstract: Ankylosing spondylitis (AS) is associated with high cardiovascular morbidity and mortality. Recent studies indicate that microvascular dysfunction may underlie cardiovascular risk in AS. We hypothesized, that microvascular morphology and dysfunction is linked to AS activity and is modifiable by TNF-α inhibitor (TNFi) treatment. Functional Laser Doppler Flowmetry with post-occlusive reactive hyperemia, and structural nailfold capillaroscopy were performed in 54 patients with AS and 28 matched controls. Active A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 44 publications
(51 reference statements)
3
20
0
Order By: Relevance
“…Over the last few years, several research groups have demonstrated that systemic inflammation plays a crucial role in promoting ED and accelerated atherosclerosis [10], thereby supporting the idea that chronic systemic inflammation may be a main contributor to the development of a dysfunctional endothelium in r-axSpA. In our study, we found that plasma inflammatory status was associated with endothelial function, a fact previously observed by van Eijk et al [14] and Batko et al [15], who showed that disease activity was related to microvascular dysfunction and that a reduction in inflammation with TNF-α blockade improved ED in r-axSpA patients. Notwithstanding, the cell determinants of such r-axSpA-associated endothelial abnormalities are unknown.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Over the last few years, several research groups have demonstrated that systemic inflammation plays a crucial role in promoting ED and accelerated atherosclerosis [10], thereby supporting the idea that chronic systemic inflammation may be a main contributor to the development of a dysfunctional endothelium in r-axSpA. In our study, we found that plasma inflammatory status was associated with endothelial function, a fact previously observed by van Eijk et al [14] and Batko et al [15], who showed that disease activity was related to microvascular dysfunction and that a reduction in inflammation with TNF-α blockade improved ED in r-axSpA patients. Notwithstanding, the cell determinants of such r-axSpA-associated endothelial abnormalities are unknown.…”
Section: Discussionsupporting
confidence: 88%
“…A variety of studies have shown that ED is a vascular abnormality frequently presented in r-axSpA patients [13][14][15], and peripheral blood mononuclear cells (PBMCs) might play a key role in its triggering, initiation, and development. In r-axSpA, T lymphocytes, a cell subtype crucial in the immune system regulation [16], have been demonstrated to be central elements in the pathology [17].…”
Section: Introductionmentioning
confidence: 99%
“… 89 Several studies have also shown systemic microvascular dysfunction as measured in peripheral vascular beds in patients with RA and AS. 72 , 90 Interesting insight into the CMD can be gained from the analysis of skin microvasculature, which has been shown to offer a useful model to study arteriole function and capillary morphology. 91 Findings from these studies are in line with earlier invasive observations that NO-mediated, acetylcholine-induced vasorelaxation in microvessels is impaired in AS and may improve with anti‐TNF-α therapy.…”
Section: Chronic Inflammatory and Autoimmune Rheumatic Disordersmentioning
confidence: 99%
“… 91 Findings from these studies are in line with earlier invasive observations that NO-mediated, acetylcholine-induced vasorelaxation in microvessels is impaired in AS and may improve with anti‐TNF-α therapy. 86 , 90 In similarity to large vessel endothelial dysfunction, microvascular dysfunction has been identified in a number of inflammatory conditions, such as severe chronic periodontitis, 92 or inflammatory bowel disease, 93 where impairment correlates with CRP. Thus, inflammation may provide a mechanistic link between these comorbidities and cardiovascular events.…”
Section: Chronic Inflammatory and Autoimmune Rheumatic Disordersmentioning
confidence: 99%
See 1 more Smart Citation